A Mini-Review of Adverse Lung Transplant Outcomes Associated With Respiratory Viruses - Bailey, Emily S.; Zemke, Juliana N.; Choi, Jessica Y.; Gray, Gregory C. (Frontiers in Immunology, 2019)
Due to their overall immunocompromised state, lung transplant recipients (LTRs) are at increased risk for the development of viral respiratory infections compared to the general population. Such respiratory infections often lead to poor transplant outcomes. We performed a systematic review of the last 30 years of medical literature to summarize the impact of specific respiratory viruses on LTRs. After screening 2,150 articles for potential inclusion, 39 manuscripts were chosen for final review. We found evidence for an association of respiratory viruses including respiratory syncytial virus (RSV), parainfluenza virus, and influenza viruses with increased morbidity following transplant. Through the literature search, we also documented associations of RSV and adenovirus infections with increased mortality among LTRs. We posit that the medical literature supports aggressive surveillance for respiratory viruses among this population.